Feasibility of producing bioethanol from cassava feedstock in the Philippines - del Rosario, Edwin E.; Ranola, Roberto F., Jr.; Demafelis, Rex B.; Elepano, Arnold R. (2010)
This paper summarizes the major results of the study to determine the feasibility of establishing a cassava plantation to supply feedstock for bioethanol processing. Crop characteristics, soil and climatic requirements, and potential of cassava as feedstock for bioethanol production are discussed. Target production areas identified by potential investors are Sarangani, South Cotabato, Sultan Kudarat, Misamis Oriental, Zambales and General Santos City. Possible contract arrangements between the distillery company and the farmer-landholder are the Corporate Farming system and the Joint Venture agreement. Plantation establishment and farm production operations are recommended to be based on proven cultural management technologies for cassava production. An estimated 10,000 ha of cassava plantation will be required to supply feedstock for a distillery plant with an annual production capacity of 30 million liters of bioethanol. Cassava tubers will be harvested from an average of 33 ha per day, at projected yields of 20 tons ha for 300 days per year of production operation. Target markets of the proposed project are distillery plants that will process the feedstock into anhydrous ethanol for use as fuel blends of oil companies. Market analysis, organization and management, and financial analysis of the proposed venture are discussed. Estimates of the project cost, financial assumptions and projections are presented. Financial indicators used are: return on investment (ROI), average net income (ANI), internal rate of return (IRRI), payback period (PBP), and net present value (NPV). Sensitivity analyses are prepared to determine the effect of cost and return parameters on the financial indicators for the production ventures.
Keywords: Biofuel; Cassava Industry; Feasibility studies